EFFECT OF MONO-VALENT ANIONS ON ACTIVE, PASSIVE TENSIONS AND TENSION EQUILIBRIUM LENGTH OF GASTROCNEMII OF UROMASTIX HARDWICKII - Azeem, Abdul; Azmat, Aisha; Shaikh, Hilal Ahmed (Pakistan Journal of Physiology, 2006)
Background: The length tension relationship has been used to determine the contractile and elastic state of the muscle. However, the shape of the active and passive tensions has been found to vary from muscle to muscle and in different animals as well. It depends upon the muscle architecture and specific function it performs. The change in the state of a skeletal muscle produced under the influence of chemical agents is not evaluated for the parameters obtained from the length tension relation. Methods: In the present study an attempt has been made to observe the effects of mono-valent anion on the contractile characteristics of isolated Gastrocnemius muscles of Uromastix. Results: The results demonstrated that both the active and passive tensions changed on treatment with mono-valent anions with a shift in their curves. This change was statistically significant for active tensions. Further, Tension equilibrium length (TEL) also affected significantly. Conclusion: It is concluded that length tension parameter, TEL < resting length (Lo) is also a useful indicator of muscle state representing dominant elasticity under the influence of mono-valent anions. It can be used to express the state of different contractile and elastic characters of the skeletal muscle.